The effect of tourism on crime in Italy: A dynamic panel approach - Bianca Biagi; Maria Giovanna Brandano; Claudio Detotto (Kiel Institute for the World Economy (IfW), 2012)
The purpose of this paper is to demonstrate that, all else being equal, for the case of Italy, tourist areas tend to have a greater amount of crime than non-tourist areas in the long run. Following the literature of the economics of crime à la Becker (1968) and Ehrlich (1973) and using a system GMM approach for the time span 1985-2003, the authors empirically test whether total crime in Italy is affected by tourist arrivals. Findings confirm the initial intuition of a positive relationship between tourism and crime in destinations. When controlling for the difference between tourists and residents in the propensity to be victimized, no relevant differences are found: the likelihood to be victimized is quite similar for the two groups. As a consequence, agglomeration and urbanisation effects seem to be the main explanation for the impact of tourism on crime. One can image that overcrowded cities provide more opportunities to criminals to commit illegal activities regardless of the number of visitors and residents in destinations.
Keywords: D62; K00; L83; 330; Tourism; crime; externalities